The Quintuple Helix Model: Cooperation system for a sustainable electric power industry in Mexico - González-Carrasco, Verónica; Robina-Ramírez, Rafael; Gibaja-Romero, Damián-Emilio; Sánchez-Oro Sánchez, Marcelo (Frontiers in Sustainable Energy Policy, 2023)
Introduction Achieving an energy transition in the power industry in Mexico is a complex task. Despite being one of the most promising countries in Latin America and the world for developing wind and solar photovoltaic energy, energy and climate change efforts are insufficient; therefore, changes are generated slowly and leisurely. This article attempts to make a proposal based on the Quintuple Helix Model as an analytical and decision-making framework to encourage the production and consumption of clean/renewable electric energy and reduce GHG emissions. It proposes the sum of strategic interactions to promote a cooperation system and knowledge transfer, know-how, and innovation through the active and committed collaboration of government, academia, industry, civil society, and the environment to achieve the sustainable development of the electricity industry in Mexico. Methods These hypotheses are the result of the development of a singular methodology based on Partial Least Squares (PLS), according to Structural Equation Modeling (SEM). The results point out that the five-helix approach is valid to solve the energy transition problem in the electricity industry in Mexico. Discussion Although it is not fully developed and consolidated, it can be replicated in scenarios with similar socioeconomic characteristics. Furthermore, the government is the most opportune intermediary driving agent for the development of the energy transition in the electricity industry, since it is the one that can lead and drive the energy transition process by modifying the electricity sector through structural change in the energy market.